Kajian Morfometri Dan Karakteristik Kualitas Air Danau Siombak Kelurahan Paya Pasir Kecamatan Medan Marelan Kota Medan Morphometry study and Characteristics Water Quality of The Siombak Lake at Paya Pasir Wards Medan Marelan Sub District Medan city. - Sarah Diba Sandy; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The Siombak lake is an artificial lake that formed as a result of sanddredging activities. The Siombak lake is near with the coast and influencedby ups and downs. The purpose from this study is to known themorphometry aspects of Siombak lake and to known the condition of theSiombak lake waters. This study was conducted over three months themonth of May to July 2014 in the waters of the Siombak lake, Paya PasirWards, Medan Marelan sub district, Medan City. The methods of research indata collection of morphometry is decisive for retrieval. The dimensionalsurface measurement is done by surrounding the periphery of the lake byusing a GPS (Global Positioning System) device. The subsurfacedimensional measurement carried out by measuring the depth of the topeweight scale that helped with the small ship. In the water sampling donethree time at five stations. Based on the results obtained, the Siombak lakehas a surface area of maximum length (Lmax) 740,3 meters, maximumwidth (Wmax) 708,3 meters. The Siombak lake also have depth maximum(Zm) of about 4-5 meters at high tide and 3-4 meters at low tide. TheSiombak lake waters quality with lightly polluted.Keyword : Siombak lake, Morphometry, Quality of Water.